2017
DOI: 10.3390/cryst7050128
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Supercooling Degree, Nucleation and Growth Rates, and Particle Size for Ice Slurry Crystallization in Vacuum

Abstract: Understanding the crystallization behavior of ice slurry under vacuum condition is important to the wide application of the vacuum method. In this study, we first measured the supercooling degree of the initiation of ice slurry formation under different stirring rates, cooling rates and ethylene glycol concentrations. Results indicate that the supercooling crystallization pressure difference increases with increasing cooling rate, while it decreases with increasing ethylene glycol concentration. The stirring r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Our formalism is thus capable of predicting trends over a wide range of shear rates, in a relatively computationally inexpensive manner. Experiments support that there is little effect on nucleation in the regime of low shear rates [15][16][17]. The non-monotonicity and decrease in nucleation rates due to shear agree with previous simulation studies in the literature [13,[23][24][25][26].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our formalism is thus capable of predicting trends over a wide range of shear rates, in a relatively computationally inexpensive manner. Experiments support that there is little effect on nucleation in the regime of low shear rates [15][16][17]. The non-monotonicity and decrease in nucleation rates due to shear agree with previous simulation studies in the literature [13,[23][24][25][26].…”
Section: Discussionsupporting
confidence: 88%
“…3. f + is the rate of attachment of molecules to the critical cluster, which can be calculated using Eq. (17). A typical attachment or 'jump' length λ can be assumed to be one molecular diameter [37].…”
Section: Methodology Sequencementioning
confidence: 99%
See 1 more Smart Citation
“…The authors declare no conflict of interest. Magnetic forces can induce crystallization and is a valuable strategy for chemical free reactions, together with electric field [41], pressure [42], ultrasound [43] and sonication treatment [44].…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…It is suggested that the chemical and photochemical reactivity of the compounds differs depending on their particular locations and physical states in or on the ice, with the relevant questions being whether the pollutants are present on the external surfaces of or between the ice crystals (the internal surfaces and veins or triple junctions) and whether they are dissolved, crystallized, or amorphous. ,− The micro- and macrostructure of the ice containing impurities is influenced by various factors, including the phases from which the ice nucleates and grows (vapor or liquid), pressure, and freezing temperature. , Furthermore, it has been demonstrated that the extent of the solute aggregation occurring during freezing depends on the cooling rate; for instance, Heger et al observed a concentration increase by 3 and not less than 6 orders of magnitude in the fast and slow cooling, respectively, utilizing the methylene blue indicator . The freeze-concentrated solution (FCS) is often located in between the ice crystals in the network of veins, , and it embodies a fundamental part of the heterogeneous ice matrix, in which the chemical reactivity is the highest.…”
Section: Introductionmentioning
confidence: 99%